DOSE OPTIMIZATION WITH mAs REDUCTION OF 15% USING COMPUTED RADIOGRAPHY ON RADIOGRAPHIC EXAMINATIONS PELVIC AP PROJECTION - Cahya, Intan; Irsal, Muhammad; Heru A., Nursama; Gunawati S., Shinta; Widiatmoko, Mahfud Edy (Journal of Vocational Health Studies, 2022)
Background: Routine pelvic radiograph examination commonly performed in diagnostic radiology services is a pelvic examination of anteroposterior projection (AP). This results in direct exposure to ionizing radiation to the internal organs in the lower abdomen, especially the reproductive organs. Purpose: Optimizing the dosage of AP projection pelvic radiographs. Method: Research is conducted quantitatively and used experimental approach with an analysis of 15% mAs reduction from the standard mAs value on AP projection pelvic examination on radiation dose and image quality using anthropomorphic phantoms. The radiation dose analysis uses the exposure index indicator. In contrast, the image quality uses the Visual Grading Analysis method, then it was continued with the Kappa Cohens test to determine the level of agreement between 2 respondents. Result: The exposure factor with the mAs value reduced by 15% from the standard exposure factor on the AP projection pelvic radiography affected the decrease in the value exposure index. The EI value generated from the optimization exposure factor shows a decrease to 300 EI, which means the dose produced is only half of the standard exposure factor dose but still produces an acceptable image, as evidenced by the VGA score. As an assessment of image quality. In this study, there was no significant difference with range VGA scores 1,7. Besides that, the test had the Kappa Cohens level of agreement with a value of 0.5-0.8. Conclusion: All images resulting from the 15% mAs value reduction variation can be used as a diagnostic assessment.